An approach to virtual clinical trial site visits: Lessons from the MeTeOR trial. Issue 1 (March 2023) - McHugh, Claire G.; Gottreich, Julia R.; Kumara, Mahima T.; Selzer, Faith; Collins, Jamie E.; Losina, Elena; Katz, Jeffrey N.
Abstract: Objective: To provide a framework for conducting clinical trial site visits virtually over videoconference, and to report on our experience doing so during the twelve-year follow-up of the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial. Design: Using published FDA guidance and prior literature, we created a structure for virtual site visits that prioritized monitoring for protocol compliance, safety, and data integrity. We conducted site visits in three stages: preparation for the visit, the virtual meeting itself, and follow-up. The preparation phase involved a review of relevant site-specific documents and a written report on the findings prior to the visit. The virtual visit itself was focused on any questions the site staff had about the pre-visit report, observing a mock study visit, touring physical spaces, and understanding the site staff's work environment. In the follow-up phase, we wrote a post-visit report summarizing the discussion during the visit and feedback given by the coordinating site. Results: We found that the virtual site visits conducted as part of the MeTeOR trial follow-up ran smoothly. Although we could not directly compare in-person and virtual site visits, site staff unanimously appreciated the efficiency and effectiveness of the virtual site visits. We noted that displaying physical workspaces over videoconferencing was difficult, and a notable drawback to this method. Conclusions: To our knowledge, this is the first published framework for conducting virtual clinical trial site visits. Conducting these visits virtually confer several advantages in terms of time, money, and efficiency.